Relationship between inflation and interest rates in Malaysia / Nik Noor Anita Hussin - Hussin, Nik Noor Anita (1994)
Prior to this writing, many renowned economists have tested, discussed and critized the inflation - interest rate linkage developed by the American economist, irving Fisher.